Modeling the transmembrane domain of bacterial chemoreceptors - Peach, Megan L. (Cold Spring Harbor Laboratory Press, 2002)
Bacterial chemoreceptors signal across the membrane by conformational changes that traverse a four-helix transmembrane domain. High-resolution structures are available for the chemoreceptor periplasmic domain and part of the cytoplasmic domain but not for the transmembrane domain. Thus, we constructed molecular models of the transmembrane domains of chemoreceptors Trg and Tar, using coordinates of an unrelated four-helix coiled coil as a template and the X-ray structure of a chemoreceptor periplasmic domain to establish register and positioning. We tested the models using the extensive data for cross-linking propensities between cysteines introduced into adjacent transmembrane helices, and we found that many aspects of the models corresponded with experimental observations. The one striking disparity, the register of transmembrane helix 2 (TM2) relative to its partner transmembrane helix 1, could be corrected by sliding TM2 along its long axis toward the periplasm. The correction implied that axial sliding of TM2, the signaling movement indicated by a large body of data, was of greater magnitude than previously thought. The refined models were used to assess effects of inter-helical disulfides on the two ligand-induced conformational changes observed in alternative crystal structures of periplasmic domains: axial sliding within a subunit and subunit rotation. Analyses using a measure of disulfide potential energy provided strong support for the helical sliding model of transmembrane signaling but indicated that subunit rotation could be involved in other ligand-induced effects. Those analyses plus modeled distances between diagnostic cysteine pairs indicated a magnitude for TM2 sliding in transmembrane signaling of several angstroms.